Competing in COVID era by adopting defensive marketing strategies - Kumar, Amit; Kaur, Anupriya (Gyan Management Journal, 2021)
The epidemic of novel corona virus (COVID-19) has created global health crises. Corona virus has a wide-reaching effect on almost every business.. This pandemic continues to impose the  temporary closure of businesses and to follow lockdown measures. In a short span, COVID-19  has changed the lives and livelihoods of people around the globe and enforced businesses to  understand the impact of COVID-19 on businesses and to react properly in this uncertain  situation. Businesses must realize that in this environment of fear, confusion, and concern they  need engage with their clients and use CRM tactics to get closer to their customers. Businesses  are facing various challenges regarding consumer demand and marketing, sales growth, and  revenue earning. This drastic event has slow down the pace of businesses and their strategies to  attract new customers for business, therefore, raised the importance of defensive marketing  strategies (Holding existing customers or customer retention). The current article provides businesses some insights to understand and implement defensive marketing strategies in and  after the time of COVID-19.
Keywords: Defensive marketing; COVID-19; Corona virus; Customer retention